Differential Coloration, Pigment Biosynthesis-Related Gene Expression, and Accumulation According to Developmental Stage in the ‘Enbu’ Apple - Van Giap Do; Seonae Kim; Youngsuk Lee; Sangjin Yang; Jeong-Hee Kim; Nay Myo Win; Young-Soon Kwon; Juhyeon Park; Jong-Taek Park (Horticulturae, 2023)
Coloration, a major factor contributing to apple quality, attracts consumer attraction, thereby increasing the sale of fruits in the market. Among the fruit pigments, anthocyanins and carotenoids are the most important pigments that impart coloration to apples. Pigment accumulation, which is regulated by transcriptional factors in the anthocyanin and carotenoid biosynthesis pathways, varies according to genetics, transcription, and developmental stage. To understand the regulation of color development in apples, we evaluated the expression of the genes in the anthocyanin and carotenoid biosynthetic pathways and analyzed the accumulation of pigment, including anthocyanin and carotenoid in the skin and flesh of the red-fleshed apple ‘Enbu’ cultivar at different fruit development stages (30, 60, 90, 120, and 150 days after full bloom, and ripe). Color development increased according to the developmental stage, with considerable variation in both the transcript levels and pigment concentrations observed in tissues, skin, and flesh. Moreover, we identified key transcription factors among the anthocyanin and carotenoid biosynthesis genes that regulated pigment accumulation. Pearson’s correlation analysis showed a strong correlation between the coloration patterns and the expression levels of anthocyanin biosynthesis-related genes (MdPAL, MdCHI, and MdF3H) and carotenoid biosynthesis-related genes (MdGGPPS, MdPSY, MdZDS, MdCRTISO, MdCRHβ, and MdZEP). This study provides insight into the molecular mechanisms underlying pigment biosynthesis for breeding high-quality red-fleshed apple varieties to cater to consumer attention and preference.